Comparison of investigator-reported and centrally adjudicated heart failure outcomes in the EMPEROR-preserved trial : heart failure - Carson, Peter; Teerlink, John R.; Komajda, Michel; Anand, Inder; Packer, Milton; Butler, Javed; Doehner, Wolfram; Ferreira, João Pedro; Filippatos, Gerasimos; Haass, Markus; Miller, Alan; Pehrson, Steen; et al. (JACC Heart failure, 2025)
Background - There is limited published information on outcome adjudication in heart failure (HF) trials, particularly in heart failure with preserved ejection fraction (HFpEF). - Objectives - The study sought to compare investigator reports with clinical events committee (CEC) adjudication and assess the impact of the SCTI (Standardized Data Collection for Cardiovascular Trials) criteria. - Methods - In the EMPEROR-Preserved (EMPagliflozin outcome tRial in Patients with chronic heart Failure With Preserved Ejection Fraction) trial, we compared investigator reports with CEC for concordance, treatment effect on primary composite outcome events and components (first event primary heart failure hospitalization [HHF] or cardiovascular [CV] mortality), prognosis after first HHF, total HHF, and trial duration with and without SCTI criteria. - Results - The CEC confirmed 67.4% investigator-reported events for the primary outcome (CV mortality 82.7%, HHF 66.3%). The HR for treatment effect did not differ between adjudication methods for the primary outcome: investigator reports (HR: 0.77; 95% CI: 0.69-0.87), CEC (HR: 0.79; 95% CI: 0.69-0.90), its components, or total HHFs. The prognosis after the first HHF for all-cause mortality and CV mortality also did not differ between investigator reports and the CEC, nor did investigator reports and HHFs with a different CEC cause. SCTI criteria were present in 92% of CEC HHFs with a similar treatment effect to non-SCTI criteria. The investigator-reported primary events reached the protocol target number 6 months earlier than the CEC (7 months with full SCTI criteria). - Conclusions - Investigator adjudication is an alternative to a CEC with similar accuracy and faster event accumulation in HFpEF. The use of granular (SCTI) criteria did not improve trial performance. Our data suggest that a broader definition of an HHF event could be particularly beneficial in HFpEF clinical trials. (EMPagliflozin outcome tRial in Patients with chronic heart Failure With Preserved Ejection Fraction; NCT03057951).